Calcification of hydrophilic intraocular lenses: Laboratory analysis and surgical technique for intraocular lens exchange. Issue 4 (October 2017) - Phogat, Jitender; Rathi, Manisha; Verma, Ritesh; Marwah, Nisha; Sachdeva, Sumit; Dhull, Chand Singh
Abstract : N/A: We present 2 cases of calcification of posterior chamber intraocular lenses (IOLs) that presented to the outpatient department of our institute with diminution of vision a few months after successful cataract surgery. Intraocular lens exchange with a hydrophobic IOL was performed in both cases, resulting in a restoration of vision.